R3HDM4 influences kidney renal clear cell carcinoma progression, immune modulation, and potential links to the IGSF8 immune checkpoint - Sun, Kai; Li, Rong; Xu, Ting; Wen, Song; Xu, De-chang; Wang, Ke-run (Frontiers in Immunology, 2025)
BackgroundR3HDM4, or R3H domain containing 4, is a gene with uncertain functions but is frequently investigated for its potential cellular roles and associations with various diseases. Kidney renal clear cell carcinoma (KIRC ), a prevalent and aggressive form of kidney cancer, currently lacks effective treatment options. This study aimed to clarify the involvement of R3HDM4 in KIRC pathogenesis.Methods and resultsAn integrated pan-cancer approach was employed to analyze data from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), ArrayExpress, and the International Cancer Genome Consortium (ICGC ), systematically assessing the prognostic relevance, clinical associations, signaling pathways, DNA methylation patterns, immune infiltration profiles, and chemotherapeutic sensitivity linked to R3HDM4 expression. Bioinformatics analyses, supported by immunohistochemistry, Western blotting (WB), and reverse transcription-quantitative polymerase chain reaction (RT-qPCR), revealed significant upregulation of R3HDM4 in KIRC tissues compared to normal controls. Kaplan–Meier (KM) survival analysis indicated that elevated R3HDM4 expression correlated with poor clinical outcomes. Single-cell RNA sequencing identified cancer cells and dendritic cells as the primary sources of R3HDM4 within the KIRC tumor microenvironment. Functional assays using R3HDM4-targeting siRNA demonstrated that its depletion suppressed the proliferative, migratory, and invasive capabilities of KIRC cells. At the molecular level, R3HDM4 knockdown attenuated epithelial–mesenchymal transition (EMT), as evidenced by increased E-cadherin expression and reduced levels of vimentin and matrix metalloproteinases MMP-2 and MMP-9. Comprehensive immune profiling revealed significant correlations between R3HDM4 expression and several immunological parameters, including immune cell infiltration, immune checkpoint expression, tumor mutational burden (TMB), and microsatellite instability (MSI). Notably, silencing of R3HDM4 led to increased expression of Immunoglobulin Superfamily Member 8 (IGSF8).ConclusionsThese analyses identify R3HDM4 as a critical oncogenic driver in KIRC, potentially acting through two mechanisms: promoting tumor growth and metastasis while also exerting immunomodulatory effects, possibly mediated by IGSF8. This suggests a potential role for IGSF8 in regulating immune checkpoints, though this remains speculative. These findings highlight R3HDM4’s potential as both a prognostic biomarker and a therapeutic target in KIRC.